Hygiene Factors and Motivation Factors towards Job Satisfaction in Malaysia Healthcare Sector - Yip Pui, Yin; Wong Boon, Yew; Gan, Wenjing (INTI International University, 2024)
Healthcare professionals' job satisfaction is a measure that should be included in quality improvement programmes for healthcare services. It significantly affects how productive and effective healthcare facilities are. The most valuable resource in the healthcare system is its human resources, which also serve as the driving force behind the delivery of sustainable services (Saari and Judge, 2004). The effectiveness of health services is impacted by employee turnover and absenteeism, which are both linked to poorer job satisfaction among these competent health professionals. The WHO has determined that the threshold of the health workforce density is currently below expectations in several developing nations. The goal of this study is to have a better awareness and knowledge of the motivational factors that influence job satisfaction in Malaysia's healthcare industries. Many academic researchers have studied motivational factors causing job satisfaction in different populations. The scope of this study will be focused on the Malaysian healthcare industry, and the respondents will be Malaysian healthcare professionals. This study concentrates on the national level of job satisfaction and motivational factors among healthcare professionals. The findings of the study help the Malaysian Ministry of Health, regional health bureaus, and other stakeholders who invest in the Malaysian health sector plan appropriate interventions to promote healthcare professionals' retention in public health sectors.